2017
DOI: 10.4103/0974-2727.199630
|View full text |Cite
|
Sign up to set email alerts
|

Role of p16/INK4a and Ki-67 as specific biomarkers for cervical intraepithelial neoplasia: An institutional study

Abstract: BACKGROUND:P16/INK4a and Ki-67 have emerged as important biomarkers for the detection of high-risk human papilloma virus (HR-HPV) associated dysplastic changes in the cervical biopsy samples. The increasing inter- and intra-observer variability in the diagnosis of dysplastic lesions and immature squamous metaplasia on histopathology has led to the advent of these biomarkers. This study was taken up with an aim to study their role in increasing the diagnostic accuracy in equivocal cases on histopathology.MATERI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 14 publications
5
15
0
Order By: Relevance
“…It was also observed that Ki67 expression was extending into the superficial third of the epithelial layer while LSIL demonstrated Ki67 expression which was limited to the basal third. These findings were similar to those by Srivastav S. et al and Hebbar A. et al (22,23).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was also observed that Ki67 expression was extending into the superficial third of the epithelial layer while LSIL demonstrated Ki67 expression which was limited to the basal third. These findings were similar to those by Srivastav S. et al and Hebbar A. et al (22,23).…”
Section: Discussionsupporting
confidence: 93%
“…Recently p16 has gained popularity not only in typing the lesion but also in predicting treatment response (21). Several authors have studied p16 expression using different positivity criteria in both preinvasive and invasive squamous carcinomas (22)(23)(24)(25). In this present study the grading used for p16 positivity, was proposed by Songkhun V. et al and later used by Alshenawy H. et al (12,20).…”
Section: Discussionmentioning
confidence: 86%
“…The low sensitivity of Pap smears and low specificity of HPV testing by HybridCapture2 are other factors which signifies the importance of the biomarkers. The role of HR-HPV in the causation of cervical dysplasias and neoplasia further helps to identify the utility of these markers, especially p16INK4a as its high expression is known to correlate with the prevalence of HR-HPV types (Hebbar and Murthy, 2017 ;Jiang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although the screening programs using pap smears are highly successful and being used routinely in some countries, a significant number of cases of cervical cancer have still been missed which can be attributed to false negative test results due to sampling errors, inter and intra observer variability [7].…”
Section: Introductionmentioning
confidence: 99%